2023
DOI: 10.1093/pnasnexus/pgad080
|View full text |Cite|
|
Sign up to set email alerts
|

Visual policy narrative messaging improves COVID-19 vaccine uptake

Abstract: In the face of vaccine hesitancy, public health officials are seeking more effective risk communication approaches to increase vaccination rates. We test the influence of visual policy narratives on COVID-19 vaccination behavior through a panel survey experiment conducted in early 2021 (n = 3,900) and then 8 weeks later (n = 2,268). We examine the effects of three visual policy narrative messages that test the narrative mechanism of character selection (yourself, your circle, and your community) and a nonnarra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 47 publications
1
5
0
Order By: Relevance
“…A second narrative, portraying a nonaudience firefighter hero, has no statistically significant effect. This finding confirms the importance of the audience's identification with a narrative's character for narrative transportation and persuasion (Jones, 2014;Raile et al, 2022;Shanahan et al, 2023). In addition, it demonstrates the power of the audience-as-hero character, even in comparison to one of the most heroic characters, the firefighter.…”
Section: Discussionsupporting
confidence: 69%
See 2 more Smart Citations
“…A second narrative, portraying a nonaudience firefighter hero, has no statistically significant effect. This finding confirms the importance of the audience's identification with a narrative's character for narrative transportation and persuasion (Jones, 2014;Raile et al, 2022;Shanahan et al, 2023). In addition, it demonstrates the power of the audience-as-hero character, even in comparison to one of the most heroic characters, the firefighter.…”
Section: Discussionsupporting
confidence: 69%
“…A narrative with the audience as a hero is, therefore, expected to have more persuasive power than a narrative portraying another hero. Recent NPF studies have situated the target audience as a hero (Raile et al, 2022;Shanahan et al, 2023) and found that messages featuring the audience as a hero were effective in influencing policy opinion. However, these studies kept the audience as a hero constant and did not compare audience-as-hero narratives with narratives portraying other heroes.…”
Section: T H E Na R R At I V E Pol Ic Y F R a M Ewor K A N D T H E Po...mentioning
confidence: 99%
See 1 more Smart Citation
“…A recent study aimed at identifying effective communication strategies to boost vaccination rates examined the impact of different messages on COVID-19 vaccine acceptance. 42 These messages included those highlighting vaccine safety, personal benefits, benefits to others, and the return to normalcy. The study revealed that the most effective message focused on personal health benefits.…”
Section: Implication Of Shifting From Free Covid-19 Vaccination To a ...mentioning
confidence: 99%
“…The success of the public health vaccination program is contingent on a simple narrative on the role of vaccines to protect the individual, their circle of contacts and their community. [49] Vaccine messaging is crucial. Simply providing individuals with more vaccine and disease information was shown in one study to increase misperceptions or reduce vaccination intention.…”
Section: Improving Vaccine Accessmentioning
confidence: 99%